Effects of the COVID‐19 pandemic on 2020 spring turkey hunting across the United States. (11th May 2022) - Danks, Zachary D.; Schiavone, Michael V.; Butler, Adam B.; Fricke, Kent; Davis, Alicia; Cobb, David T.
Abstract: Spring wild turkey ( Meleagris gallopavo ) hunting is a foundational activity for many hunters across North America. Managing turkey hunters and turkey hunting is, therefore, a priority for state and provincial fish and wildlife management agencies. Early stages of the current SARS‐CoV‐2 (COVID‐19) pandemic in the United States coincided with 2020 spring turkey hunting seasons across the U.S. Potential effects of increases in peoples' time available for hunting on effort and turkey populations could have been substantial. We surveyed the primary wildlife biologist tasked with wild turkey management for each state and provincial jurisdiction with a huntable wild turkey population to determine turkey hunter and hunting dynamics before and during the spring 2020 turkey season. Biologists in 47 states responded to the survey. Results varied among states but hunting license sales, the number of hunters afield, harvest, total hunter‐days afield, and the number of days individual hunters were afield were greater in 2020 than the mean from the previous 3 years (2017–2019) in many states. Although hunting effort and total reported harvest increased in most states in 2020 from the previous 3‐year average, take‐per‐unit‐effort (i.e., harvest per hunter day) decreased in 93% of jurisdictions from which data were available, supporting the finding that increases in turkey harvest in spring 2020 were a result of a COVID‐related increase in participation and effort and not increases in turkey abundance. We recommend using these reference data for turkey population and turkey hunter monitoring pre‐ and post‐pandemic. Monitoring efforts should include wildlife population and habitat evaluations and study of hunter dynamics in a social science framework. Abstract : We evaluated turkey hunter and hunting dynamics before and during the spring 2020 turkey season corresponding with the outbreak of the 2020 COVID‐19 pandemic. Hunting license sales, the number of hunters afield, harvest, total hunter‐days afield, and the number of days individual hunters were afield increased in 2020. Although hunting effort and total reported harvest increased in most states, take‐per‐unit‐effort decreased in 93% of jurisdictions, supporting the finding that increases in turkey harvest in spring 2020 were a result of a COVID‐related increase in participation and effort and not increases in turkey abundance.